A revision of Geostachys (Zingiberaceae: Alpinioideae) in Cambodia, Laos and Vietnam, including a new species, G. aristata - Leong-Škorničková, Jana; Quốc Bình, Nguyễn; Đăng, Trần Hữu; Trường, Lưu Hồng; Nuraliev, Maxim S. (Phytotaxa, 2023)
A revision of the ginger genus Geostachys (Zingiberaceae: Alpinioideae: Alpinieae) in Cambodia, Laos and Vietnam is presented. Three species are formally recognised, all endemic to the area of study, including one new species from central Vietnam. Lectotypes are designated for G. annamensis and G. pierreana. The uncertainty about the type locality of G. pierreana is highlighted; the absence of this species in Thailand and Vietnam is demonstrated. The presence of Geostachys in Laos is discussed. The key to the species of the genus is provided. For each species, description, notes on etymology/eponymy, distribution, IUCN preliminary assessment, habitat and phenology, and taxonomy are given. The newly described species, G. aristata, is compared to the morphologically closest congener, G. annamensis, from which it differs by green leaf sheaths and ligules, greenish bracts and bracteoles with prominently aristate apices, prominently mucronate calyx lobes and labellum with crimson spots extending to the margins.